Optimizing Elementary School Education through the Implementation of Karawitan-Based Learning Grounded in Local Wisdom (Journal of Basic Education Research, 2024)
Purpose of the study: This research aims to identify the optimization of the implementation of learning based on local musical wisdom in arts and culture music material subjects in elementary schools. Methodology: This research uses a classroom action research approach as the main method. The research subjects in this context are fifth grade elementary school students who are involved in learning based on Karawitan Local Wisdom. The data collection technique in this research uses a questionnaire to measure responses and observation sheets to measure student learning activity. The data analysis technique uses descriptive statistics and the independent sample t-test. Main Findings: The research results show that the implementation of Karawitan Local Wisdom-based learning at the Sendangsari Village Elementary School, through a project-based and open approach, has had a significant positive impact on students' responses and their activeness in the learning process. There is a real increase in students' interest, understanding and appreciation of the learning material, along with more intensive student participation. Novelty/Originality of this study: The novelty of the results of this research lies in the implementation of a Karawitan Local Wisdom-based learning model at the elementary school level, which concretely depicts significant changes in students' responses and their activeness during the learning process.